ASSOCIATION OF SELF-REPORTED HOSPITAL DISCHARGE HANDOFFS WITH 30-DAY READMISSIONS - Oduyebo, Ibironke (2013)
BACKGROUND: Poor provider communication across health care settings may lead to adverse outcomes. We sought to determine the frequency with which inpatient providers report communicating directly with outpatient providers and whether direct communication was associated with 30-day readmissions. METHODS: We included the initial hospitalization for consecutive patients discharged from the Medicine service at a large, academic medical center from September, 2010 to December, 2011. Self-reported communication was captured from a mandatory electronic discharge worksheet field. Thirty day readmissions, length of stay (LOS), and demographics were obtained from administrative databases. We used multivariable logistic regression models to examine, first, the association between direct communication and patient age, sex, LOS, race, payer, expected 30-day readmission rate based on diagnosis and illness severity, and physician type and, second, the association between 30-day readmission and direct communication, adjusting for patient and physician-level factors. RESULTS: Of 13,954 hospitalizations, 6,635 met inclusion criteria. Successful direct communication occurred in 2,438 (36.7%). The most frequently reported reason for lack of direct communication was the provider’s perception that the discharge summary was adequate. Predictors of direct communication, adjusting for all other variables, included patients cared for by hospitalists without house-staff (OR = 1.81; 95% CI 1.59-2.08), high expected 30-day readmission rate (OR = 1.18, 1.10-1.28 per 10%), and insurance by Medicare (OR = 1.35; 95% CI 1.16-1.56) and private insurance companies (OR = 1.35; 95% CI 1.18-1.56) compared to Medicaid. Direct communication with the outpatient provider was not associated with readmissions (OR = 1.08, 0.92-1.26) in adjusted analysis. CONCLUSIONS: Self-reported direct communication between inpatient and outpatient providers occurred at a low rate, but was not associated with readmissions. This suggests that enhancing inter-provider communication at hospital discharge may not, in isolation, prevent readmissions.